Effects of Heat Generation/Absorption On A Stagnation Point Flow Over a Stretching Surface In Porous Medium With Convective Boundary Conditions - Muhammad Khairul Anuar, Mohamed; Nor Aida Zuraimi, Md Noar; Mohamad Imran, Anwar; Mohd Zuki, Salleh; Anuar, Ishak (Jurnal KALAM, 2014)
In this study, the mathematical modeling for heat generation/absorption effects on a stagnation point flow over a stretching surface in porous medium, with convective boundary conditions is considered. The non linear partial differential equations are transformed to the ordinary differential equations by similarity transformation before being solved numerically using the Runge-Kutta Fehlberg method. Numerical solutions are obtained for the surface temperature, heat transfer coefficient, local Nusselt number and skin friction coefficient as well as the velocity and temperature profiles. The features of the flow and heat transfer characteristics for various values of the permeability parameter, heat source/sink parameter, Prandtl number, stretching parameter and conjugate parameter are analyzed and discussed.